National resources and environment (Wisma Sumber Asli) / Azinuddin Azlani ... [et al.] - Azlani, Azinuddin; Arip, Lukhman; Mohamad, Mohamad Safri Azwadi; Ramli, Najmi Maisarah; Ja’afar, Nor Afidah; Abdul Rashid, Nur Liyana (2013)
Ministry of Natural Resources and Environment (NRE) is located at Natural Resources, 25 Persiaran Perdana, Presint 4, Putrajaya, and Federal Territory of Putrajaya, Malaysia. The Prime Minister established the Ministry of Natural Resources & Environment (NRE) on March 27, 2004 following the formation of a new cabinet. There are 17 floors of offices, two basements, one of ground floor level and one rooftop so the building has 22 floors in total. The height of the building is 77m. This building had built by Putrajaya Holdings (PJH) and NRE bought the building as a ministry office. The expenditure for site rental is RM 7, 532, 973, 03 every four months. There are some facilities provided in the building of which are prayer room, offices, meeting rooms, library, and gymnasium and so on. These facilities made for employees, make their feel more comfortable, and can facilitate their work. ‘Surau’ has built for Muslims to perform their prayers. The capacity of the ‘Surau’ is 100 people can fit in the ‘Surau’ in one time.